Pengaruh Kepemimpinan Kepala Sekolah dan Manajemen Sumber Daya Manusia terhadap Produktivitas Kerja Guru di SDIT Darul Athfal Jakarta - Nur Aidah, Alfira; Izfanna, Duna; andayani, Rika H (UIN Mahmud Yunus Batusangkar, 2025)
This study aims to determine how principal leadership and human resource management can influence teacher work productivity at SDIT Darul Athfal Jakarta. A thorough understanding of the factors of teacher work productivity is crucial for the implementation of principal leadership and human resource management. This study used a quantitative approach by distributing questionnaires as a data collection method. The questionnaires were distributed to all 34 teachers at SDIT Darul Athfal Jakarta. The results showed that principal leadership influenced teacher work productivity by 8.9%. And human resource management on teacher work productivity by 49.6%. Meanwhile, principal leadership and human resource management on teacher work productivity by 63.9%